Tannin extract foam material with electromagnetic shielding function and preparation method thereof

By preparing a combination of modified gum resin and functional conductive nanomaterials, the template method and carbonization process are used to solve the shortcomings of existing electromagnetic shielding materials in terms of environmental adaptability and versatility, and high-performance, environmentally friendly and degradable electromagnetic shielding materials are achieved, and excellent electromagnetic shielding efficiency and thermal insulation performance are provided.

CN114173543BActive Publication Date: 2025-03-25SOUTHWEST FORESTRY UNIVERSITY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202110366207.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-04-06
Publication Date
2025-03-25
Estimated Expiration
2041-04-06

AI Technical Summary

Technical Problem

The existing electromagnetic shielding materials have shortcomings in the adaptability and versatility of the use environment, especially in the context of low-carbon, environmentally friendly and efficient utilization of renewable resources, the research on lightweight breathable electromagnetic shielding materials has not yet been fully developed.

Method used

By preparing a candle foam material with electromagnetic shielding function, the template method and carbonization process are used, combined with modified candle resin and functional conductive nanomaterials, the uniform distribution of the conductive material on the foam hole wall is achieved, and the electromagnetic shielding performance of the material is improved.

Benefits of technology

It realizes high-performance, environmentally friendly and degradable electromagnetic shielding materials, with excellent electromagnetic shielding efficiency, flame retardancy and thermal insulation performance, and is suitable for a wide range of applications of multimedia and electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114173543B_ABST
    Figure CN114173543B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electromagnetic shielding materials and preparation, and specifically relates to a tannin extract foam material with electromagnetic shielding function and a preparation method thereof; tannin extracts are modified to prepare tannin extract resin, which is then mixed with functional conductive nanomaterials to prepare electromagnetic shielding foam material, so that the conductive material is evenly distributed on the cell wall, and the electromagnetic shielding function of the foam material is realized due to the special microporous structure of the tannin extract foam material. At the same time, the foam material has better flame retardant and heat preservation properties through the modification of the tannin extract, thereby expanding the application range and meeting the new requirements of the electromagnetic shielding material, thereby obtaining a high-performance, environmentally friendly and degradable electromagnetic shielding material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic shielding materials and preparation thereof, and in particular relates to a tannin foam material with electromagnetic shielding function and a preparation method thereof. Background Art

[0002] With the development of information technology, electronic multimedia products are widely used. Electromagnetic waves, as a carrier of information transmission, inevitably bring electromagnetic pollution. Electromagnetic wave interference has a great harm to the normal use of electrical equipment, radio communication systems and human health. Therefore, it is required to: ① limit the power lines or magnetic lines within a certain area; ② make a certain area unaffected by external power lines and magnetic lines, so as to further reduce the harm caused by electromagnetic pollution and interference.

[0003] In the field of electromagnetic shielding materials, the shielding body can usually be made of materials such as copper, aluminum, steel, and ferrite. With the development of composite material technology, the common electromagnetic shielding material nowadays is a conductive composite material obtained by physically blending conductive fillers and resin matrices. Both the traditional metal-based electromagnetic shielding materials and the rapidly developing carbon-based electromagnetic shielding materials have good electromagnetic shielding effects. With the implementation of low-carbon, environmentally friendly, and efficient utilization of renewable resources policies and the improvement of consumer awareness, the multifunctional development of materials has attracted more and more attention. Lightweight and breathable electromagnetic shielding materials have gradually become a new research hotspot.

[0004] Tannin resin foam material is a material with 95% renewable raw materials. It has great application potential in thermal insulation, packaging, industry, transportation, military, aerospace industrial-grade daily necessities and other fields due to its light weight, good flame retardancy, good thermal insulation and high specific strength. It can replace the polyurethane foam, polystyrene foam and phenolic resin foam that are now widely used commercially.

[0005] Many new conductive nanomaterials such as carbon nanotubes, nanocarbon black, graphene and carbon nanofibers are gaining more and more attention due to their structural characteristics of ultra-high aspect ratio and large specific surface area, as well as excellent electrical and mechanical properties. However, if carbon nanomaterials are not filled properly, they are prone to agglomeration in the resin matrix, thus limiting their advantages in structure and performance.

[0006] The patent document with application number CN201810659125.3 discloses an electromagnetic shielding material, including a polymer matrix and a graphene-biochar composite filler dispersed in the polymer matrix, which includes, by weight percentage: 0.05-10% graphene, 0.05-20% biochar, and 70-99.9% polymer matrix. Among them, the polymer matrix is ​​any one of polyvinyl alcohol, polycarbonate or polyamide, or a mixture of at least two of them, and the biochar is any one of sawdust, bamboo chips, rice husks, straw or coconut shells, or a mixture of at least two of them, obtained by pyrolysis carbonization and activation treatment. However, its main raw material is a polymer matrix, and the polyamide used is a non-degradable material.

[0007] The patent document with application number CN201910039939.1 discloses a method for preparing a carbon nanotube / graphene / polymer electromagnetic shielding material, which is obtained by impregnating a three-dimensional carbon nanotube / graphene composite in a high molecular polymer precursor and curing it. The oxidized carbon nanotube / graphene composite can also be placed in a tubular furnace, heated to 800-1200°C at a rate of 5-20°C / min, and calcined at high temperature for 0.5-4h under the protection of an inert gas. However, it is also prepared using a polymer as a precursor, especially containing natural rubber, and the calcination temperature is 800-1200°C. At this temperature, natural rubber will decompose, resulting in poor structural properties of the prepared material.

[0008] In order to achieve the adaptability of electromagnetic shielding materials to the use environment, meet the new requirements of electromagnetic shielding materials, and give the materials more functional properties, it is extremely necessary to develop high-performance electromagnetic shielding materials. Summary of the invention

[0009] In order to solve the above problems, the present invention provides a tannin extract foam material with electromagnetic shielding function and a preparation method thereof.

[0010] This is achieved specifically through the following technical solutions:

[0011] 1. A tannin extract foam material with electromagnetic shielding function, which is composed of 10-30 parts of tannin extract, 10-20 parts of furfuryl alcohol, 5-10 parts of cross-linking agent, 8-20 parts of catalyst, 5-30 parts of water, and 0.1-1.5 parts of conductive material by weight.

[0012] Furthermore, the content of tannin in the tannin extract is ≥70%.

[0013] Furthermore, the cross-linking agent includes but is not limited to formaldehyde, glyoxal and glutaraldehyde.

[0014] Furthermore, the catalyst is a p-toluenesulfonic acid solution with a concentration of 50-65%.

[0015] Furthermore, the conductive material includes but is not limited to carbon nanotubes, nano carbon black and graphene.

[0016] 2. The preparation method of the above-mentioned tannin extract foam material with electromagnetic shielding function comprises the following steps:

[0017] (1) Preparation of modified tannin resin:

[0018] After the tannin extract, furfuryl alcohol, water, crosslinking agent and catalyst are fully stirred, the conductive material is added, and the mixture is fully stirred for 9-12 minutes under the action of ultrasound with a power of 1000-1800W to make the conductive nanomaterial evenly dispersed in the modified tannin extract resin;

[0019] (2) Formwork pouring:

[0020] Select the ready-made open-cell polyurethane foam as the template, and completely immerse the template into the prepared modified tannin resin to achieve full penetration of the resin into the open-cell template. The immersion time can be adjusted according to the thickness of the template to achieve full immersion and penetration. Take out the template and dry it until the modified tannin resin on the template skeleton no longer drips.

[0021] (3)Carbonization process:

[0022] The template dried in step (2) is placed in a carbonization furnace and carbonized under nitrogen protection. After the carbonization furnace reaches the end temperature, the temperature is kept constant for 1-3 hours. After the treatment is completed, the carbonization furnace is closed and cooled to room temperature under nitrogen protection to obtain a tannin foam material with electromagnetic shielding function.

[0023] Furthermore, the terminal temperature is 800-1000°C, and the heating rate is 5-20°C / min.

[0024] In summary, the beneficial effects of the present invention are as follows: the present invention prepares tannin extract resin by modifying tannin extract, and then mixes it with functional conductive nanomaterials to prepare electromagnetic shielding foam material, so that the conductive material is evenly distributed on the cell wall, and the electromagnetic shielding function of the foam material is realized due to the special microporous structure of the tannin extract foam material. At the same time, the foam material has better flame retardant and thermal insulation properties through the modification of tannin extract, which expands the application range, meets the new requirements of electromagnetic shielding materials, and obtains a high-performance, environmentally friendly and degradable electromagnetic shielding material.

[0025] Among them, the electromagnetic shielding material of the present invention is carbonized by a carbonization process after being immersion-formed by a template method, and the foam will not fall off, and the addition of conductive materials has no obvious effect on the flame retardancy of tannin resin. The conductive nanomaterials can be evenly distributed on the pore walls of the tannin resin foam, and the obtained foam material has excellent electromagnetic shielding function. The innovation of the present invention lies in the use of the template method instead of directly using tannin resin for foaming, which is also a significant difference from the existing tannin resin foam preparation technology. And during the test, it was found that the tannin foam material prepared by the present invention not only has a higher electromagnetic shielding efficiency value, but also has good flame retardancy and thermal insulation properties. It can be directly used in the field where multimedia and electronic components are widely used to prevent electrical equipment from being interfered with and reduce the harm of electromagnetic waves to the human body. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a template structure diagram of tannin foam material with electromagnetic shielding function after resin impregnation, with a magnification of X10. DETAILED DESCRIPTION

[0027] The specific embodiments of the present invention are further described in detail below, but the present invention is not limited to these embodiments, and any improvement or substitution based on the basic spirit of the present embodiment still falls within the scope of protection required by the claims of the present invention.

[0028] Example 1

[0029] 1. A tannin extract foam material with electromagnetic shielding function, which is composed of 20 parts of tannin extract, 10 parts of furfuryl alcohol, 10 parts of cross-linking agent, 10 parts of catalyst, 30 parts of water and 1.0 part of conductive material by weight.

[0030] Furthermore, the content of tannin in the tannin extract is ≥70%.

[0031] Furthermore, the cross-linking agent is formaldehyde with a concentration of 37%.

[0032] Furthermore, the catalyst is a p-toluenesulfonic acid solution with a concentration of 65%.

[0033] Furthermore, the conductive material is multi-walled carbon nanotubes.

[0034] 2. The preparation method of the above-mentioned tannin extract foam material with electromagnetic shielding function comprises the following steps:

[0035] (1) Preparation of modified tannin resin:

[0036] After the tannin extract, furfuryl alcohol, water, crosslinking agent and catalyst are fully stirred, the conductive material is added, and the mixture is fully stirred for 10 minutes under the action of ultrasound with a power of 1800 W to make the conductive nanomaterial evenly dispersed in the tannin extract resin;

[0037] (2) Formwork pouring:

[0038] Select a ready-made open-cell polyurethane foam with a pore size of 300 μm as a template, and completely immerse the template into the prepared modified tannin resin for 30 minutes to achieve full penetration of the resin into the open-cell template. Take out the template and dry it until the tannin resin on the template skeleton no longer drips.

[0039] (3)Carbonization process:

[0040] The template dried in step (2) is placed in a carbonization furnace and carbonized under nitrogen protection. After the carbonization furnace reaches the end temperature, it is kept at a constant temperature for 2 hours. After the treatment is completed, the carbonization furnace is closed and cooled to room temperature under nitrogen protection to obtain a tannin foam material with electromagnetic shielding function.

[0041] Furthermore, the end temperature is 900°C and the heating rate is 10°C / min.

[0042] Example 2

[0043] 1. A tannin extract foam material with electromagnetic shielding function, which is composed of 10 parts of tannin extract, 15 parts of furfuryl alcohol, 10 parts of cross-linking agent, 8 parts of catalyst, 10 parts of water and 0.3 parts of conductive material by weight.

[0044] Furthermore, the content of tannin in the tannin extract is ≥70%.

[0045] Furthermore, the cross-linking agent is hexamethylenetetramine with a concentration of 30%.

[0046] Furthermore, the catalyst is a p-toluenesulfonic acid solution with a concentration of 60%.

[0047] Furthermore, the conductive material is graphene.

[0048] 2. The preparation method of the above-mentioned tannin extract foam material with electromagnetic shielding function comprises the following steps:

[0049] (1) Preparation of modified tannin resin:

[0050] After the tannin extract, furfuryl alcohol, water, crosslinking agent and catalyst are fully stirred, the conductive material is added, and the mixture is fully stirred for 12 minutes under the action of ultrasound with a power of 1500 W to make the conductive nanomaterial evenly dispersed in the tannin extract resin;

[0051] (2) Formwork pouring:

[0052] Select a ready-made open-cell polyurethane foam with a pore size of 300 μm as a template, and completely immerse the template into the prepared modified tannin resin for 30 minutes to achieve full penetration of the resin into the open-cell template. Take out the template and dry it until the tannin resin on the template skeleton no longer drips.

[0053] (3)Carbonization process:

[0054] The template dried in step (2) is placed in a carbonization furnace and carbonized under nitrogen protection. After the carbonization furnace reaches the end temperature, it is kept at a constant temperature for 1 hour. After the treatment is completed, the carbonization furnace is closed and cooled to room temperature under nitrogen protection to obtain a tannin foam material with electromagnetic shielding function.

[0055] Furthermore, the end temperature is 800°C and the heating rate is 5°C / min.

[0056] Example 3

[0057] 1. A tannin extract foam material with electromagnetic shielding function, which is composed of 15 parts of tannin extract, 20 parts of furfuryl alcohol, 8 parts of cross-linking agent, 10 parts of catalyst, 15 parts of water and 0.3 parts of conductive material by weight.

[0058] Furthermore, the content of tannin in the tannin extract is ≥70%.

[0059] Furthermore, the cross-linking agent is glutaraldehyde with a concentration of 50%.

[0060] Furthermore, the catalyst is a p-toluenesulfonic acid solution with a concentration of 50%.

[0061] Furthermore, the conductive material is nano carbon black.

[0062] 2. The preparation method of the above-mentioned tannin extract foam material with electromagnetic shielding function comprises the following steps:

[0063] (1) Preparation of modified tannin resin:

[0064] After the tannin extract, furfuryl alcohol, water, crosslinking agent and catalyst are fully stirred, the conductive material is added, and the mixture is fully stirred for 9 minutes under the action of ultrasound with a power of 1800 W to make the conductive nanomaterial evenly dispersed in the tannin extract resin;

[0065] (2) Formwork pouring:

[0066] Select a ready-made open-cell polyurethane foam with a pore size of 300 μm as a template, and completely immerse the template into the prepared modified tannin resin for 30 minutes to achieve full penetration of the resin into the open-cell template. Take out the template and dry it until the tannin resin on the template skeleton no longer drips.

[0067] (3)Carbonization process:

[0068] The template dried in step (2) is placed in a carbonization furnace and carbonized under nitrogen protection. After the carbonization furnace reaches the end temperature, it is kept at a constant temperature for 2 hours. After the treatment is completed, the carbonization furnace is closed and cooled to room temperature under nitrogen protection to obtain a tannin foam material with electromagnetic shielding function.

[0069] Furthermore, the end temperature is 1000°C and the heating rate is 10°C / min.

[0070] Example 4

[0071] 1. A tannin extract foam material with electromagnetic shielding function, which is composed of 30 parts of tannin extract, 20 parts of furfuryl alcohol, 7 parts of cross-linking agent, 20 parts of catalyst, 30 parts of water and 1.5 parts of conductive material by weight.

[0072] Furthermore, the content of tannin in the tannin extract is ≥70%.

[0073] Furthermore, the cross-linking agent is glyoxal with a concentration of 55%.

[0074] Furthermore, the catalyst is a p-toluenesulfonic acid solution with a concentration of 65%.

[0075] Furthermore, the conductive material is carbon nanofiber.

[0076] 2. The preparation method of the above-mentioned tannin extract foam material with electromagnetic shielding function comprises the following steps:

[0077] (1) Preparation of modified tannin resin:

[0078] After the tannin extract, furfuryl alcohol, water, crosslinking agent and catalyst are fully stirred, the conductive material is added, and the mixture is fully stirred for 12 minutes under the action of ultrasound with a power of 1000 W to make the conductive nanomaterial evenly dispersed in the tannin extract resin;

[0079] (2) Formwork pouring:

[0080] Select a ready-made open-cell polyurethane foam with a pore size of 300 μm as a template, and completely immerse the template into the prepared modified tannin resin to achieve full penetration of the resin into the open-cell template. Soak for 40 minutes, take out the template, and dry it until the tannin resin on the template skeleton no longer drips.

[0081] (3)Carbonization process:

[0082] The template dried in step (2) is placed in a carbonization furnace and carbonized under nitrogen protection. After the carbonization furnace reaches the end temperature, it is kept at a constant temperature for 3 hours. After the treatment is completed, the carbonization furnace is closed and cooled to room temperature under nitrogen protection to obtain a tannin foam material with electromagnetic shielding function.

[0083] Furthermore, the end temperature is 800°C and the heating rate is 20°C / min.

[0084] Comparative Example 1

[0085] The tannin extract foam material was prepared by using the raw material ratio and preparation method of Example 1, except that no conductive material was added.

[0086] The thermal insulation performance, flame retardancy and electromagnetic shielding effect of the tannin extract foam materials prepared in Examples 1-4 and Comparative Example 1 were tested. The results are shown in Table 1.

[0087] Table 1

[0088]

[0089] As shown in Table 1, the thermal conductivity coefficient of the electromagnetic shielding functional foam material prepared by the present invention is lower than that of the comparative example, and it has excellent thermal insulation. The addition of the conductive material has no obvious effect on the flame retardancy of the tannin resin, which is specifically manifested in that the oxygen index is basically unchanged. It is particularly noteworthy that after the conductive nanomaterial is added and evenly distributed on the pore wall of the tannin resin foam, the foam material has a higher electromagnetic shielding efficiency value, indicating that the tannin resin has a very excellent electromagnetic shielding function after adding the functional conductive nanomaterial, and meets the requirements of the civil standard for electromagnetic shielding materials.

[0090] Comparative Example 2

[0091] The foam material is prepared according to the method and formula of Example 1, except that tannin extract with a tannin content of less than 60% is selected as the raw material.

[0092] Experimental results: When tannin extracts with a tannin content of less than 60% are used as raw materials, the viscosity is too low. When the foam material is cast using the template method, a large amount of tannin extract resin falls down and cannot be well formed and fixed on the original foam skeleton.

[0093] Comparative Example 3

[0094] The foam material was prepared according to the method and formula of Example 1, except that the amount of tannin extract was changed to 5 parts and 45 parts respectively.

[0095] Experimental results: When the amount of tannin extract is about 5 parts, the foam is too brittle and the slag rate is significantly increased. When the amount of tannin extract is 45 parts, the viscosity of the tannin extract resin is too high and it is difficult to operate.

[0096] Comparative Example 4

[0097] The foam material was prepared according to the method and formula of Example 1, except that phenolic resin was used instead of tannin extract to prepare the foam material.

[0098] Experimental results: The electromagnetic shielding efficiency of the foam material is only about 10dB. Even after adding conductive materials, the conductive materials are very easy to agglomerate in the phenolic resin, which affects the electromagnetic shielding rate.

[0099] In addition, when phenolic resin was used instead of tannin extract for experiments, it was found that the use of phenolic resin as a raw material would greatly increase the cost, and the process of preparing the foam material needed to be maintained in a certain constant temperature environment, which also increased the production cost.

Claims

1. A tannin extract foam material with electromagnetic shielding function, characterized in that: The invention is composed of the following raw materials in parts by weight: 10-30 parts of tannin extract, 10-20 parts of furfuryl alcohol, 5-10 parts of crosslinking agent, 8-20 parts of catalyst, 5-30 parts of water and 0.1-1.5 parts of conductive material; wherein the content of tannin in the tannin extract is ≥70%; The tannin extract foam material is prepared by fully stirring tannin extract, furfuryl alcohol, water, a cross-linking agent and a catalyst, adding a conductive material, and preparing a modified tannin extract resin through ultrasonic treatment, and then preparing the tannin extract resin through template casting and carbonization process; the template casting is to select an open-cell polyurethane foam as a template, completely immerse the template in the prepared modified tannin extract resin, fully soak and penetrate, take out the template, and air-dry until the modified tannin extract resin on the template skeleton no longer drips; the carbonization process is to put the template into a carbonization furnace, carbonize it under nitrogen protection, heat the carbonization furnace to the end temperature, and then treat it at a constant temperature for 1-3 hours, and cool it to room temperature under nitrogen protection, so as to obtain the tannin extract foam material with electromagnetic shielding function.

2. The tannin extract foam material with electromagnetic shielding function as claimed in claim 1, characterized in that: The cross-linking agent includes formaldehyde, glyoxal and glutaraldehyde.

3. The tannin extract foam material with electromagnetic shielding function as claimed in claim 1, characterized in that: The catalyst is a p-toluenesulfonic acid solution with a concentration of 50-65%.

4. The tannin extract foam material with electromagnetic shielding function as claimed in claim 1, characterized in that: The conductive material includes carbon nanotubes, nano carbon black and graphene.

5. The method for preparing a tannin extract foam material with electromagnetic shielding function as claimed in claim 1, characterized in that: The ultrasonic treatment is to fully stir for 9-12 minutes under the action of ultrasonic waves with a power of 1000-1800W.

6. The method for preparing a tannin extract foam material with electromagnetic shielding function as claimed in claim 1, characterized in that: The terminal temperature is 800-1000°C, and the heating rate is 5-20°C / min.

Citation Information

Patent Citations

  • An electromagnetic shielding material, its preparation method and applications

    CN108794812B

  • Carbon nanotube / graphene / polymer electromagnetic shielding material, preparation method and application thereof

    CN109762339A

  • Preparation method of graphene multilayer foam carbon material

    CN105271177A

  • Thermal insulation fireproof material and preparation method thereof

    CN111333801A

  • Conductive electromagnetic shielding paint and application thereof

    CN1490363A